Analisis Kolaborasi Siswa Kelas V SD Melalui Model Pembelajaran Think Pair Share - Sekarwati Nur Aisyah; Heru Purnomo; Rian Nurizka (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2024)
This research aims to determine student collaboration through the Think Pair Share learning model for fifth grade students at SD Muhammadiyah Ambarbinangun. This type of research is qualitative. The method used is descriptive. The data collection technique used in this research is an observation sheet. The data analysis process was carried out using a descriptive approach that described the data in the form of narratives and percentages. The results of the research show that collaboration among class V students at SD Muhammadiyah Ambarbinangun reached a level that meets the specified criteria, namely 85.41% proportionally. From this data, there was 1 student who received a good predicate with a percentage of 75% and 11 other students had a very good predicate. The learning carried out by the teacher applies the think pair share type cooperative learning model.